The role of Pentadienoic growth regulator acid by number of growth regulators in the initiation, growth and differentiation of Nigella sativa Callus - Hanna Abdallah; Rehab Albaker (College of Education for Pure Sciences, 2005)
The effect of Pentadienoic acid (PDA) as a synthetic growth regulator, on the induction, growth and differentiation of callus from stem segments of seedlings of black seed Nigella sativa L. was carried out. PDA was used at the concentrations 10"4, 10 and 10"8 molar alone, or with the optimal concentration of Benzyl Adenine (BA) which is 10"3 molar,and that for Dichlorophenoxyacetic acid (2,4-D) 1 0 molar. The results showed that the addition of PDA alone to the nutritional medium disencourage the induction of callus , However when PDA was added along with the optimal concentrations of the standard growth regulators, the best growth of callus obtained on the medium supplied wHh(10" ) molar of each of 2,4-D and PDA.Thu; fresh weight of callus reached (25.6) gm at 100 days age .it was found also that the addition of BA with PDA encourages growth of shoots since the first stage of the growth, with the stimulation of the callus growth also ,but the presence of 2,4-D with PDA does not encourage any differentiation except the induction and growth of the callus.